2001
DOI: 10.1091/mbc.12.6.1843
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Vb Is Associated with Plasma Membrane Recycling Systems

Abstract: Myosin Va is associated with discrete vesicle populations in a number of cell types, but little is known of the function of myosin Vb. Yeast two-hybrid screening of a rabbit parietal cell cDNA library with dominant active Rab11a (Rab11aS20V) identified myosin Vb as an interacting protein for Rab11a, a marker for plasma membrane recycling systems. The isolated clone, corresponding to the carboxyl terminal 60 kDa of the myosin Vb tail, interacted with all members of the Rab11 family (Rab11a, Rab11b, and Rab25). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
465
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(486 citation statements)
references
References 52 publications
20
465
0
Order By: Relevance
“…Endosomes or endocytic transport vesicles likely use cytoskeletal elements for motility (Durrbach et al, 1996;Nakagawa and Miyamoto, 1998;Durrbach et al, 2000;Neuhaus and Soldati, 2000;Lanzetti et al, 2001;Lapierre et al, 2001;Zaslaver et al, 2001;Shupliakov et al, 2002;Engqvist-Goldstein and Drubin, 2003). Actinin-4 is predicted to have an actin-binding domain, and we have observed that it binds actin (our unpublished data).…”
Section: Actinin-4 Depletion Affects Tf Traffickingsupporting
confidence: 53%
“…Endosomes or endocytic transport vesicles likely use cytoskeletal elements for motility (Durrbach et al, 1996;Nakagawa and Miyamoto, 1998;Durrbach et al, 2000;Neuhaus and Soldati, 2000;Lanzetti et al, 2001;Lapierre et al, 2001;Zaslaver et al, 2001;Shupliakov et al, 2002;Engqvist-Goldstein and Drubin, 2003). Actinin-4 is predicted to have an actin-binding domain, and we have observed that it binds actin (our unpublished data).…”
Section: Actinin-4 Depletion Affects Tf Traffickingsupporting
confidence: 53%
“…39,40 Myosins are known to transport proteins in neurons through binding to their C-terminal globular domain, 41 and MYO5B specifically regulates vesicle trafficking. 42 Strikingly, MYO5B has been shown to regulate EGFR cycling in both canine (MDCK) and human cells (A431). 43 In light of the current associations with both MYO5B and EGFR, the functional relationship of these two genes may point to a possible molecular pathway (that is, vesicle trafficking at the plasma membrane) in which converging susceptibility alleles of small effect size, in distinct component genes, may underlie the biological etiology of BP disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids of CXCR2, 331T, IL323,324/AA, enhanced green fluorescent protein (EGFP)-Rab11a, full-length EGFP-myosin Vb, EGFP-myosin Vb tail, full-length EGFP-Rab11-FIP2, EGFP-Rab11-FIP2 (129 -512), and DsRed2-myosin Vb tail were constructed as described previously (Mueller et al, 1995;Fan et al, 2001b;Lapierre et al, 2001;Hales et al, 2002).…”
Section: Plasmidsmentioning
confidence: 99%